DEVELOPMENT AND CHARACTERIZATION OF AN APIS MELLIFERA HONEYMEAD FROM PARÁ FLAVORED WITH NUTMEG (REMUNOM, 2026)
Mead is a fermented alcoholic beverage made from honey, still relatively unexplored in Brazil,especially when associated with the valorization of regional ingredients. The use of spices such asnutmeg can represent an alternative for product diversification and value addition. Thus, this studyaimed to develop and characterize, from a physicochemical point of view, a mead produced withhoney from Apis mellifera from northeastern Pará, flavored with nutmeg (Myristica fragrans) atdifferent fermentation times (10, 20, and 30 days). Initially, the honey and nutmeg were characterizedin terms of physicochemical parameters, ensuring the quality of the raw materials. Subsequently, abase mead was produced, followed by the addition of nutmeg and further fermentation. Thephysicochemical analyses performed on the meads included pH, electrical conductivity (EC), density,viscosity, alcohol content, total soluble solids (TSS), titratable acidity, and dry residue, with statisticaltreatment of the data. The results indicated that the addition of nutmeg increased the pH and ECvalues and reduced the viscosity, while the alcohol content and TSS did not undergo significantchanges. Titratable acidity was the variable most influenced by the flavoring time, showing adecreasing linear behavior. Thus, nutmeg exerts a relevant influence on the physicochemicalcharacteristics of mead, highlighting acidity as a possible indicator of the beverage's preparationtime.